STUDI MODEL PEMBELAJARAN PROBLEM SOLVING TERHADAP MOTIVASI BELAJAR MATEMATIKA - Laoli, Arnius; Harefa, Amin Otoni (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research is based on a preliminary study conducted by researchers, found problems, namely (1) Mathematics is often considered a difficult subject to understand (2) Mathematics is a subject that is considered the most difficult, most boring and often considered the most difficult subject. scary and (3) the number of complaints from students about math lessons that are difficult, uninteresting and boring. study aims to describe the study of problem solving learning models on the motivation to learn mathematics whether or not it can improve mathematics learning outcomes. This type of research is library research (Library Research). Widiasworo, (2018:30) said